2017
DOI: 10.1111/1748-5967.12238
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant secondary metabolites on common cutworm, Spodoptera litura (Lepidoptera: Noctuidae)

Abstract: The effect of various flavonoids, lectins and phenyl β‐D‐glucoside on larval survival, weights and the activities of digestive (total serine protease and trypsin) and detoxifying (esterase and glutathione‐S‐transferase) enzymes of Spodoptera litura larvae at 7 days after treatment was studied through diet incorporation assay. Flavonoids (rutin, chlorogenic acid, quinic acid, caffeic acid, naringenin, quercitin, kaempferol, myricetin, catechin, and ferulic acid) were incorporated in artificial diet at 100, 500 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 48 publications
2
33
0
Order By: Relevance
“…The demand for pesticides is growing, and scientists have focused on flavonoids for pesticides, as they prevent pest larval growth through enzymes inhibition 16 . Off all the flavonoids, Kr and Qu are the most important pest repellent molecules, and reports show that kaempferol-3,7-diglucoside can be used as a Mamestraconfigurata deterrent, and Qu can be used for Spodopteralitura larvae 17 , 18 . Kr and Qu are strong antioxidants and are highly efficient free radical scavengers.…”
Section: Introductionmentioning
confidence: 99%
“…The demand for pesticides is growing, and scientists have focused on flavonoids for pesticides, as they prevent pest larval growth through enzymes inhibition 16 . Off all the flavonoids, Kr and Qu are the most important pest repellent molecules, and reports show that kaempferol-3,7-diglucoside can be used as a Mamestraconfigurata deterrent, and Qu can be used for Spodopteralitura larvae 17 , 18 . Kr and Qu are strong antioxidants and are highly efficient free radical scavengers.…”
Section: Introductionmentioning
confidence: 99%
“…Freshly picked gallnuts should be blanched in boiling water in time, and when the surface turns from yellowish brown to gray, immediately removed from the water and dried in the sun or low fire. Studies have shown that the volatile substances of the spring host plant play a pivotal role in the long-distance location of insects, especially in the host transfer period [ 17 , 18 ]. K. rhusicola has strong host plant specificity [ 16 ], which suggests that R. potaninii may release particular volatiles that attract K. rhusicola .…”
Section: Introductionmentioning
confidence: 99%
“…However, olfactory receptors are also present on ovipositor, tarsi or both, and have been reported to be involved in the choice of oviposition site, feeding and communication between conspecific individuals (Ahmed et al 2013;Stadler et al 1995;Zhang et al 2012). Selection of a suitable host for egg laying plays an integral role in the survival of offspring because most larvae and nymphs showed limited mobility (Harris et al 2001;Su et al 2018). The setae that are commonly present on the arthropods tarsal region are usually involved in temperature, humidity, and chemoreception.…”
Section: Introductionmentioning
confidence: 99%
“…The setae that are commonly present on the arthropods tarsal region are usually involved in temperature, humidity, and chemoreception. Selection of a suitable host for egg laying plays an integral role in the survival of offspring because most larvae and nymphs showed limited mobility (Harris et al 2001;Su et al 2018). To date, the ovipositor and tarsal morphology of several insects of economic importance have been studied.…”
Section: Introductionmentioning
confidence: 99%